Highly sensitive fluorescence detection of glycoprotein based on energy transfer between CuInS2 QDs and rhodamine B. (10th April 2015) - Gao, Xue; Li, Dan; Tong, Ying; Ge, Dan; Tang, Yiwei; Zhang, Defu; Li, Jianrong
Abstract: A highly sensitive fluorescence method for glycoprotein detection has been established based on fluorescence resonance energy transfer (FRET) between CuInS2 quantum dots (QDs) and rhodamine B (RB). Lectins comprise a group of proteins with unique affinities toward carbohydrate structures, so the process of FRET can occur between lectin‐coated QDs (CuInS2 QDs–Con A conjugates, acceptors) and carbohydrate‐coated RB (RB–NH2 ‐glu conjugates, donors). The fluorescence of lectin‐coated QDs was recovered in the presence of a glycoprotein such as glucose oxidase (GOx) and transferrin (TRF), which significantly reduced the FRET efficiency between the donor and the acceptor. Under optimal conditions, a linear correlation was established between the fluorescence intensity ratio I 654 / I 577 and the TRF concentration over the range of 6.90 × 10 ‐10 to 3.45 × 10 ‐8 mol/L, with a detection limit of 2.5 × 10 ‐10 mol/L. The linear range for GOx is 3.35 × 10 ‐10 to 6.70 × 10 ‐8 mol/L, with a detection limit of 1.5 × 10 ‐10 mol/L. The proposed method was applied to the determination of glycoprotein in human serum and cell‐extract samples with satisfactory results. Furthermore, CuInS2 QDs–Con A conjugates are used as safe and efficient optical nanoprobes in HepG2 cell imaging. Copyright © 2015 John Wiley & Sons, Ltd.